Implementation Of Article 45 Of Law Number 1 Of 1974 Concerning Marriage Related To The Fulfillment Of Children's Rights Post-Divorce Based On The Principle Of Legal Certainty - Yudha Ginanjar (JURNAL HUKUM SEHASEN, 2024)
The legal perspective regarding Law Number 1 of 1974 concerning Marriage (Marriage Law) has undergone changes through Law Number 16 of 2019, as in Article 45 of Law Number 1 of 1974 which regulates providing children's rights after divorce. The implementation of Article 45 of Law Number 1 of 1974 concerning Marriage regarding providing children's rights after divorce can vary in practice, depending on the context and policies implemented by the institution or institution that handles divorce cases. The legal basis for educating children's rights after divorce is based on the Marriage Law and the Compilation of Islamic Law (KHI) which involves the 1945 Constitution of the Republic of Indonesia and the Basic Principles of the Convention on the Rights of the Child which was approved in 1990. This research is based on scientific allegations that protection and the interests of children are given less attention in divorce settlements. In a marriage relationship, problems often arise which lead to divorce. Many things are triggering factors, and usually the victims are children. This research aims to analysed the application of the principle of legal certainty mandated in Article 45 of Law Number 1 of 1974 concerning Marriage. The research method used is a normative juridical research method by taking material from statutory regulations, literature and legal journals.